Pete the Cat's 12 groovy days of Christmas - Dean, Kim, 1969-; Dean, James, 1957-; Litwin, Eric (New York : Harper, an Imprint of HarperCollins Publishers, 2018)
Pete and his friends are rockin' and groovin' while counting down the days to Christmas! Who needs five golden rings, when you can have five onion rings?
Keywords: Pete, -- the Cat (Fictitious character) -- Juvenile fiction; Gifts -- Juvenile fiction; Animal fiction; Christmas fiction; Picture books